2021
DOI: 10.3390/atmos12010079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CFD and Multizone Modeling from Contaminant Migration from a Household Gas Furnace

Abstract: In Central and Eastern Europe, a growing popularity of gas heaters as the main source of heat and domestic hot water can be observed. This is the result of new laws and strategies for funding that have been put in place to encourage households to stop using coal and replace it with cleaner energy sources. However, there is a growing concern that gas furnaces are prone to malfunction and can be a threat to occupants through CO (carbon monoxide) generation. To see how a faulty gas furnace with a clogged exhaust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Figure 1 displays the HVAC system in the operating room, (a) filter in air handling unit (AHU) system to filter dirty air coming from the mixing air cabin, (b) cooling coil to cool down the temperature of the air with chilled water on the coil that comes from the process of cooling the water by the chiller, (c) heating coil for the process of heating and humidifying the air to fit with the design of the operating room, (d) fan to supply the air into the room, (e) HEPA filter to filter the air particles with the efficiency of HEPA filters over 99.97% (above 0.5 µm) so that the air entering the room becomes clean, (f) return air; the air coming from the room draughts to the AHU system and supplies the operating room. [18]. The results revealed that the location of the furnace could influence contaminant accumulation and migration.…”
Section: System Descriptionmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 1 displays the HVAC system in the operating room, (a) filter in air handling unit (AHU) system to filter dirty air coming from the mixing air cabin, (b) cooling coil to cool down the temperature of the air with chilled water on the coil that comes from the process of cooling the water by the chiller, (c) heating coil for the process of heating and humidifying the air to fit with the design of the operating room, (d) fan to supply the air into the room, (e) HEPA filter to filter the air particles with the efficiency of HEPA filters over 99.97% (above 0.5 µm) so that the air entering the room becomes clean, (f) return air; the air coming from the room draughts to the AHU system and supplies the operating room. [18]. The results revealed that the location of the furnace could influence contaminant accumulation and migration.…”
Section: System Descriptionmentioning
confidence: 94%
“…The improvement in indoor air quality (IAQ) was also conducted by the measurement and CFD simulations that are shown as valid tools for IAQ indication [17]. In addition, CFD modeling of contaminant migration in a household gas furnace was investigated by Szczepanik-Scislo [18]. The results revealed that the location of the furnace could influence contaminant accumulation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that accumulation of CO in a garage also elevated the levels of CO inside an attached household and that ventilation strategies have a large effect on the contaminant migration [19]. However, in this previous study, only natural ventilation was used.…”
Section: Introductionmentioning
confidence: 89%
“…Because of its potential to quickly impact human health and even endanger human life, it was taken as a priority out of the contaminants that would occur in such a scenario. In a previous study, it was shown that a faulty exhaust line from the furnace not only resulted in a rise in CO in the room where the furnace was installed, but also in the adjoining building [19]. According to the World Health Organization (WHO), a person should not be subjected to a concentration of CO higher than 30 ppm (0.000055) in 1 h or 9 ppm (0.000017 kg/kg) during a period of 8 h [41].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation